Digital Evangelism and the Mediatization of Nigerian Pentecostalism: New Media and the Transformation of Religious Communication in the Twenty-First Century - Victor Taiwo Odewale (European Scientific Journal, ESJ, 2026)
The rapid proliferation of digital communication technologies has significantly reshaped the structure and practice of religion worldwide. Nigerian Pentecostal churches have emerged as particularly innovative adopters of new media platforms for evangelism, religious instruction, and global networking. This article examines how digital media—including social networking platforms, livestreaming technologies, and digital broadcasting systems—have reshaped religious authority, worship practices, and transnational expansion within Nigerian Pentecostalism. Drawing on mediatization theory, globalisation theory, and religious economy theory, the study analyses the digital communication strategies of major Nigerian Pentecostal ministries. The article argues that digital evangelism has enabled Nigerian Pentecostal churches to transcend geographical boundaries and build global religious communities, while also generating new challenges, including commercialisation, exploitation, doctrinal fragmentation, and the virtualisation of worship, which leads to the fragmentation of African community life. The study contributes to the growing scholarship on digital religion and the globalisation of African Christianity.